ANALISIS FAKTOR RISIKO KEJADIAN DEMAM TIFOID PASIEN RAWAT INAP DI RUMAH SAKIT KABUPATEN KEBUMEN TAHUN 2013 - , RINA HUDAYANI, Prof. dr. Hari Kusnanto, Dr.PH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Typhoid fever is a disease caused by infection of Salmonella typhoid and paratyphoid bacteria. There are 350-810 people who get this disease per 100.000 people andthe percentage of death is 0.6-5%. Typhoid fever in Kebumen Regency always belongs to the big five diseases. The criteria are the number of in-patient in the hospital and the extraordinary occurrence for 4 years (from 2007 to 2010). This disease is related to unhealthy sanitation and bad individual hygiene practice. This research is aimed to analyze the risk factors of typhoid fever occurrence in inpatient in Kebumen Public Hospital in 2013. Method :The type of this research is analytical observational research with control case study design. The sample was taken by using consecutive samplingmethod and there were 148 respondents, consisting of 74 case respondentsand 74 control respondents. The data were analyzedby usingMcNemar (bivariate) test and conditional logistic regression (multivariate). Results : Most respondents are in the age of 15-20 years old (32.43%), female (70.27%), the graduates of Senior/Vocational High School (29.05%) andstudent/university student (34.46%). The results of multivariable analysis are the risk factor of eating non-homemade snack habit is high (p=0.000